Parent decision toward measles, mumps, rubella vaccination and its associated factors based on protective motivation theory - Andiko Nugraha Kusuma; Tukimin Sansuwito; Milawati Lusiani (International Journal of Public Health Science (IJPHS), 2023)
Childhood vaccination provides direct protection through community immunity, while also contributing to population-level disease protection. The purpose of this study was to determine parents' decision on measles, mumps, rubela (MMR) vaccination and the factors that influence their decisions. This study used a cross-sectional study in a community setting in Banten, Indonesia. The protection motivation theory (PMT) scale incorporates interpersonal factors, prior experience, MMR information sources, threat appraisal, and coping appraisal. A multivariate logistic regression was utilized to determine the factors related with the parent's decision. A total of 220 people volunteered to participate in this study, of which 45.5% (n=100) accepted the MMR vaccine on time, 22.7% (n=50) accepted it late, and 31.8 % (n=70) received no MMR vaccine at all. Those who accept MMR vaccine on time were more likely to had secondary and below of education level, interpersonal characteristics, treat appraisal, coping appraisal, past experience, and MMR knowledge and sources than those who did not accept MMR vaccine. The present study, which employed Protection Motivation Theory, provided valuable insights into the factors that influence parents' intentions to adhere with the official MMR vaccine advice in a Banten region with a high measles prevalence.